Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Que vivent les femmes d'Afrique? - Boni, Tanella (Cyclo, 2008)
Les Africaines du XXIe siècle ne restent pas recluses sur des territoires connus : la maternité qui semble les définir et la cuisine où elles passent du temps. Pour faire face aux problèmes de survie quotidienne, elles se donnent le droit de penser par elles-mêmes, de concevoir, d'imaginer des solutions, de prendre des initiatives. Elles bravent les barrières et les obstacles en "attachant leurs pagnes". Au coeur de l'Afrique en crise, théâtre de mille conflits, elles sont prêtes à prendre leurs responsabilités et à jouer un rôle de premier plan y compris en économie et en politique. Dans une mosaïque de situations multiples, Tanella Boni nous offre ainsi un tableau contrasté des femmes africaines, comme le sont elles-mêmes les Afriques. Un avenir s'y dessine, celui du courage et de la recherche d'un destin qui ne soit pas écrit de toute éternité.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; lit3220; philosophie; premier cycle; régions géographiques; sciences humaines; études sur les femmes*